2021
DOI: 10.3390/ijerph18073809
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Model of Gait Recovery at One Month after Hip Fracture from a National Cohort of 25,607 Patients: The Hip Fracture Prognosis (HF-Prognosis) Tool

Abstract: The aim of this study was to develop a predictive model of gait recovery after hip fracture. Data was obtained from a sample of 25,607 patients included in the Spanish National Hip Fracture Registry from 2017 to 2019. The primary outcome was recovery of the baseline level of ambulatory capacity. A logistic regression model was developed using 40% of the sample and the model was validated in the remaining 60% of the sample. The predictors introduced in the model were: age, prefracture gait independence, cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…There have been relatively many studies on mortality and ambulatory function after surgery according to fracture type. [24,[29][30][31][32][33][34][35][36] There was a study that showed no difference in mortality or function according to fracture type, [36] and there were rare reports that intertrochanteric fracture had worse Table 2 The evaluation of physical and cognitive function and quality of life immediately after transfer and at 6 months post-surgery (N = 165). function, [29,35] but overall, intertrochanteric fracture reported worse initial function, [24,30] mortality, [31,32] and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There have been relatively many studies on mortality and ambulatory function after surgery according to fracture type. [24,[29][30][31][32][33][34][35][36] There was a study that showed no difference in mortality or function according to fracture type, [36] and there were rare reports that intertrochanteric fracture had worse Table 2 The evaluation of physical and cognitive function and quality of life immediately after transfer and at 6 months post-surgery (N = 165). function, [29,35] but overall, intertrochanteric fracture reported worse initial function, [24,30] mortality, [31,32] and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most hospitals in Thailand do not perform MSE screening in their routine outpatient and inpatient practice. Finally, these scoring systems do not include some well-known predictive factors that serve as significant barriers to post-operative rehabilitation (e.g., concomitant fracture, post-operative ICU admission or ventilator use, and post-operative complication) [ 14 , 15 , 16 , 17 , 18 , 19 ]. Surgical techniques might be another promising prognostic factor that could have good predictive ability and should be incorporated into clinical scoring systems.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, individualized risk scoring systems have continuously emerged as a more attractive and more specific method that can improve predictive performance [ 17 , 18 , 19 ]. A few scoring systems have been developed for the prediction of post-operative functional outcomes and functional statuses, such as the simple scoring system by Hagino T. et al [ 17 ], the six risk scores by Burgos E. et al [ 23 ], the prognostic model for predicting the recovery of walking independence of elderly patients after hip-fracture surgery by Bellelli G. et al [ 41 ], and the predictive model of gait recovery at one month after hip fracture [ 16 ]. Table 5 provides specific details of the study domain, predictors used, and the definition of the clinical endpoint for each scoring system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been relatively many studies on mortality and ambulatory function after surgery according to fracture type [24,[29][30][31][32][33][34][35][36]. There was study that showed no difference in mortality or function according to fracture type [36], and there were rare reports that intertrochanteric fracture had worse function [29,35], but overall, intertrochanteric fracture reported worse initial function [24,30], mortality [31,32] and functional outcomes [24,30,33,34].…”
Section: Discussionmentioning
confidence: 99%